2014
DOI: 10.1111/1365-2435.12262
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime consequences of food protein‐carbohydrate content for an insect herbivore

Abstract: Summary1. Food protein-carbohydrate content has significant consequences for animal survival, growth and reproduction. Rarely, though, is its effect examined over an animal's entire lifetime. 2. In this study, we reared newly hatched caterpillars [Heliothis virescens Fabricus (Lepidoptera: Noctuidae)] on diets containing different protein/carbohydrate (p/c) ratios. We recorded larval survival, time to pupation, pupal mass, eclosion success, time to eclosion and pupal body lipid content. Additionally, for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
87
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 66 publications
12
87
0
1
Order By: Relevance
“…As Fig. 5 shows, this result is much more consistent with the ITs of other lepidopterans that have been measured in GF studies and most closely matches that found for H. virescens (Lee et al, 2006;Roeder and Behmer, 2014), a generalist New World species that is closely related to H. zea. These results support our initial hypothesis that the IT for H. zea would be slightly protein-biased and be similar to that of H. virescens.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As Fig. 5 shows, this result is much more consistent with the ITs of other lepidopterans that have been measured in GF studies and most closely matches that found for H. virescens (Lee et al, 2006;Roeder and Behmer, 2014), a generalist New World species that is closely related to H. zea. These results support our initial hypothesis that the IT for H. zea would be slightly protein-biased and be similar to that of H. virescens.…”
Section: Discussionsupporting
confidence: 88%
“…Since Waldbauer et al (1984), protein and carbohydrate regulation has been tested in several lepidopteran species using the GF, including Heliothis virescens (Lee et al, 2006;Telang et al, 2001;Roeder and Behmer, 2014), Heliothis subflexa (Lee et al, 2006), Manduca sexta (Thompson and Redak, 2005), Malacasoma disseria (Despland and Noseworthy, 2006), Plutella xyostella (Warbrick-Smith et al, 2009), Spodoptera exigua (Merkx-Jacques et al, 2008), Spodoptera exempta (Lee et al, 2004b), Spodoptera littoralis (Lee et al, 2004a), and Spodoptera litura (Lee, 2010). Across these species, the ITs range from slightly carbohydrate-biased ratio for S. exempta (0.8:1) to slightly protein-biased ratio for H. virescens (1.5:1) and S. littoralis (1.3:1), with several species selecting for a balanced 1:1 p:c ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the animal consistently consumes from these pairs in such a way that it obtains the same amount of the nutrient, the animal can be considered to be behaviorally adjusting its food selection to obtain a target quantity of the nutrient. Because numerous prior studies have demonstrated that intake targets (at least for carbohydrate:protein ratio) closely match the diet composition that maximizes fitness (Roeder and Behmer, 2014), these behavioral tests allow the animal itself to 'tell us' its optimal dietary phosphate level.…”
Section: Introductionmentioning
confidence: 99%
“…Animals, including insects, are known to employ compensatory mechanisms when eating foods that are nutritionally imbalanced (Simpson and Raubenheimer, 1993;Simpson et al, 2002;Cook et al, 2010) or have low-nutrient concentration (Yang and Joern, 1994;Slansky and Wheeler, 1989;Lee et al, 2004). Furthermore, multiple studies have revealed that reproductive output and lifespan are also responsive to protein and carbohydrate concentrations and ratios (Maklakov et al, 2008;Lee et al, 2008, Roeder andBehmer, 2014). …”
mentioning
confidence: 99%